(untitled) (Indonesian Health Justice Review, 2024)
The urban-rural divide in Indonesia remains a significant barrier to achieving health equality across the nation. Despite the expansion of health insurance under Universal Health Coverage (UHC), rural populations continue to experience higher morbidity and mortality rates compared to urban dwellers. This paper explores the root causes of health inequalities between urban and rural areas, analyzing factors such as socioeconomic status, geographic isolation, and disparities in healthcare infrastructure. Through a mixed-methods approach involving statistical data analysis and interviews with healthcare providers, the study identifies critical gaps in healthcare delivery, such as shortages of medical personnel, poor road access, and the high cost of transportation to healthcare facilities. The paper argues that while UHC has made strides in expanding coverage, more targeted interventions are required to address the unique needs of rural populations, particularly in terms of accessibility and quality of care. Policy recommendations include expanding mobile health services, improving rural healthcare infrastructure, and increasing investment in rural healthcare workforce development.